Analisis Penentuan Harga Jual Listrik pada PT PLN (Persero) ULP Medan Timur - Saparuddin Siregar; Nur Ainun (LPPM IAI Nasional Laa Roiba Bogor, 2023)
How is electricity marketing in increasing profits or profits at PT PLN (Persero) ULP Medan Timur and how to find out the determination of the selling price is determined based on full costs at PT PLN (Persero) ULP Medan Timur. The purpose of the research is that the PT PLN (Persero) ULP Medan Timur office can conduct electricity marketing in increasing profits or profits at the right PT PLN (Persero) ULP Medan Timur and maximize the aspect of determining the selling price determined based on full costs in the office in order to create work comfort and optimizing the performance of their employees. The research method used is a qualitative research method with direct interviews and documentation. The result of the research is the cost of sales based on electricity groups R, B, I, P, L with a cost of about ± Rp. 169/Kwh up to Rp. 1.035/Kwh. Prepaid power for family duty bunches from 2,200 VA to over 6,600 VA. US 9.90 cents per kWh. PLTP with a limit of 50-100 MW utilizes HPT plots of US 8.19 cents per kWh and for PLTP with a limit of more than 100 MW utilizes HPT plots of US 7.25 cents per kWh. Keywords: prepaid, postpaid, selling price